Comparative ecophysiological effects of drought on seedlings of the Mediterranean water-saver Pinus halepensis and water-spenders Quercus coccifera and Quercus ilex - Baquedano, F. J.; Castillo, F. J. (Trees, 2006)
Ecophysiological and structural traits of seedlings of the water-saver Pinus halepensis and the water-spenders Quercus coccifera and Q. ilex were studied in response to water stress under greenhouse conditions. Water deﬁcit reduced stomatal conductance (gs ) and, as a consequence, both net CO2 assimilation (A) and transpiration rate (E) were also reduced. Water stress also emphasized midday downregulation of the photochemical efﬁciency (dynamic photoinhibition) reducing quantum yield of noncyclic electron transport (PSII ), photochemical quenching (qP) and photochemical efﬁciency of the open reaction centres of PSII (F v /F m) and involved an increase of thermal dissipation of excess energy. However, water stress not only induced dynamic photoinhibition but also brought a reduction in Fv/Fm (chronic photoinhibition). Despite the water-saving strategy ofP. halepensisthat limited net CO2 assimilation, this species showed a higher photochemical efﬁciency and lower photoinhibition than Quercusspecies. This was not the result of a different photochemical quenching but was linked to a higher value of F v /F m, indicating a less severe photo-inactivation of PSII. Water stress resulted in a loss of pigment content and in an increase of the carotenoids/chlorophyll ratio, antioxidant capacity and the biomass rate allocated to roots as opposed to that assigned to leaves. P. halepensis showed a lower photoinhibition and antioxidant activity than Quercus species due to its lower pigment content and higher proportion of carotenoids allowing P. halepensis to use, in a more effective way, the lesser excess energy absorbed.
Keywords: antioxidant activity; chlorophyll fluorescence; gas exchange and water potential; morphological parameters; pigments

Comparative ecophysiological effects of drought on seedlings of the Mediterranean water-saver Pinus halepensis and water-spenders Quercus coccifera and Quercus ilex - Baquedano, F J; Castillo, F J (Trees, 2006)
Ecophysiological and structural traits of seedlings of the water-saver Pinus halepensis and the water-spenders Quercus coccifera and Q. ilex were studied in response to water stress under greenhouse conditions. Water deﬁcit reduced stomatal conductance (gs ) and, as a consequence, both net CO2 assimilation (A) and transpiration rate (E) were also reduced. Water stress also emphasized midday downregulation of the photochemical efﬁciency (dynamic photoinhibition) reducing quantum yield of noncyclic electron transport (PSII ), photochemical quenching (qP) and photochemical efﬁciency of the open reaction centres of PSII (F v /F m) and involved an increase of thermal dissipation of excess energy. However, water stress not only induced dynamic photoinhibition but also brought a reduction in Fv/Fm (chronic photoinhibition). Despite the water-saving strategy ofP. halepensisthat limited net CO2 assimilation, this species showed a higher photochemical efﬁciency and lower photoinhibition than Quercusspecies. This was not the result of a different photochemical quenching but was linked to a higher value of F v /F m, indicating a less severe photo-inactivation of PSII. Water stress resulted in a loss of pigment content and in an increase of the carotenoids/chlorophyll ratio, antioxidant capacity and the biomass rate allocated to roots as opposed to that assigned to leaves. P. halepensis showed a lower photoinhibition and antioxidant activity than Quercus species due to its lower pigment content and higher proportion of carotenoids allowing P. halepensis to use, in a more effective way, the lesser excess energy absorbed.
Keywords: antioxidant activity; chlorophyll fluorescence; gas exchange and water potential; morphological parameters; pigments